Ex-ante Poverty and Distributional Impacts of COVID–19 in Indonesia - Ali, Rabia; Tiwari, Sailesh (World Bank, Washington, DC, 2020)
The Government of Indonesia has responded to the pandemic strongly, instituting several economic support measures for households. Budgetary outlays on the newly announced programs amount to an approximate doubling of spending on core social assistance programs.